Efficient Diode Performance with Improved Effective Carrier Lifetime and Absorption Using Bismuth Nanoparticles Passivated Silicon Nanowires - Mariem Naffeti; Mohamed Ali Zaïbi; Alejandro Vidal García-Arias; Radhouane Chtourou; Pablo Aitor Postigo (Nanomaterials, 2022)
In this paper, we report a novel design of bismuth nanoparticle-passivated silicon nanowire (Bi@SiNW) heterojunction composites for high diode performances and improved effective carrier lifetime and absorption properties. High-density vertically aligned SiNWs were fabricated using a simple and cost-effective silver-assisted chemical etching method. Bi nanoparticles (BiNPs) were then anchored in these nanowires by a straightforward thermal evaporation technique. The systematic study of the morphology, elemental composition, structure, and crystallinity provided evidence for the synergistic effect between SiNWs and BiNPs. Bi@SiNWs exhibited an eight-fold enhancement of the first-order Raman scattering compared to bare silicon. Current–voltage characteristics highlighted that bismuth treatment dramatically improved the rectifying behavior and diode parameters for Bi-passivated devices over Bi-free devices. Significantly, Bi wire-filling effectively increased the minority carrier lifetime and consequently reduced the surface recombination velocity, further indicating the benign role of Bi as a surface passivation coating. Furthermore, the near-perfect absorption property of up to 97% was achieved. The findings showed that a judicious amount of Bi coating is required. In this study the reasons behind the superior improvement in Bi@SiNW’s overall properties were elucidated thoroughly. Thus, Bi@SiNW heterojunction nanocomposites could be introduced as a promising and versatile candidate for nanoelectronics, photovoltaics and optoelectronics.